Doxorubicin and adjudin co-loaded pH-sensitive nanoparticles for the treatment of drug-resistant cancer. (August 2019) - Wang, Qiong; Zou, Chenming; Wang, Lingying; Gao, Xueqin; Wu, Jindan; Tan, Songwei; Wu, Gang
Graphical abstract: Abstract: Multi-drug resistance (MDR) of tumor is a major cause of chemotherapy failure. In this study, a pH-sensitive graft copolymer, poly(β-amino ester)-g-β-cyclodextrin (PBAE-g-β-CD), was synthesized via Michael addition polymerization and was employed to co-deliver doxorubicin (DOX), a chemotherapy agent, and adjudin (ADD), a mitochondrial inhibitor, in the form of dual-drug co-loaded nanoparticles (NPs). Specifically, DOX was conjugated to 1-adamantaneacetic acid (Aa) to generate a prodrug that was subsequently encapsulated in the cavity of cyclodextrin via host-guest interactions. In addition, ADD was encapsulated by poly(β-aminoester) (PBAE). The introduction of the Aa- d - α -tocopheryl polyethylene glycolsuccinate (TPGS) conjugate enhanced the biocompatibility and serum stability of the resulting NPs. The NPs can realize precise ratiometric control of drugs being loaded, increase cellular uptake of the drugs, induce mitochondrial dysfunction and augment tumor treatment efficiency by inducing apoptosis. Western blot and polymerase chain reaction analyses showed that inhibition of P-glycoprotein and X-linked inhibitor of apoptosis protein expression may underlie inhibition of tumor resistance mediated by NPs. The MCF-7/ADR xenograft tumor model also revealed that in comparison with DOX, the NPs exhibited satisfactory performance in promoting apoptosis of tumor cells and achieved high therapeutic outcomes for MDR tumors. Statement of Significance: Combination chemotherapy is an effective way to overcome MDR of tumor. However, one of the major obstacles for successful combination chemotherapy is the co-loading, co-delivery and controlled release of two different drugs, whose chemo-physical properties may be totally different. In this study, a pH-sensitive NP system was designed to realize the co-loading and precise ratiometric control of DOX and ADD, as well as the programmed drug release. That is, ADD release was triggered by low pH in endo/lysosome after endocytosis and then DOX was hydrolyzed to achieve a sustained release in tumor cells. Therefore, the NPs exhibited an effectively growth inhibition against MDR cells both in vitro and in vivo via the synergistic effect of ADD and DOX, which provided a promising strategy for treatment of MDR cancer.